2018
DOI: 10.1126/science.aan4153
|View full text |Cite
|
Sign up to set email alerts
|

Notch ligand Dll1 mediates cross-talk between mammary stem cells and the macrophageal niche

Abstract: The stem cell niche is a specialized environment that dictates stem cell function during development and homeostasis. We show that Dll1, a Notch pathway ligand, is enriched in mammary gland stem cells (MaSCs) and mediates critical interactions with stromal macrophages in the surrounding niche in mouse models. Conditional deletion of Dll1 reduced the number of MaSCs and impaired ductal morphogenesis in the mammary gland. Moreover, MaSC-expressed Dll1 activates Notch signaling in stromal macrophages, increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
151
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(164 citation statements)
references
References 47 publications
6
151
2
Order By: Relevance
“…Given the conserved role of these pathways in EMT and CSCs, these axes of interaction could be relevant to other cancers associated with the dissemination of premalignant or dormant cancer cells. Of note, tissue-resident macrophages of embryonic origin also dominate the adult mammary gland in the mouse (Jäppinen et al, 2019), and recent studies have shown an important role for mammary gland macrophages in regulating the phenotype of basal stem cells (Chakrabarti et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Given the conserved role of these pathways in EMT and CSCs, these axes of interaction could be relevant to other cancers associated with the dissemination of premalignant or dormant cancer cells. Of note, tissue-resident macrophages of embryonic origin also dominate the adult mammary gland in the mouse (Jäppinen et al, 2019), and recent studies have shown an important role for mammary gland macrophages in regulating the phenotype of basal stem cells (Chakrabarti et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Other markers that further segregate luminal cells include GATA3, ErbB3, and ALDH (Asselin‐Labat et al , ; Ginestier et al , ; Shehata et al , ) in humans, while CD14 (Shehata et al , ), c‐Kit (Lim et al , ; Regan et al , ), and Elf5 (Zhou et al , ; Oakes et al , ) segregate the murine luminal compartment. Finally, Lgr5 (Van Keymeulen et al , ; Plaks et al , ), Procr (Wang et al , ), Tspan8 (Fu et al , ), Dll1 (Chakrabarti et al , ), and Bcl11b (Cai et al , ), each further enriches basal subsets for mammary stem cells, although an exclusive mammary stem cell signature remains elusive. Nuances in protocols from tissue dissociation to preferred cell surface markers and stem/progenitor readouts contribute to some discordant findings.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have demonstrated that specific macrophage subtypes play previously unanticipated roles in stem cell niche formation and modulate the maintenance of several adult tissues such as hair follicles , bone marrow , mammary gland and testis . Interestingly, the β‐gal + subpopulation of Kupffer cells was found to express Trem2 and Aif1 in a similar manner to the perifollicular macrophages that maintain hair stem cell quiescence and the microglia of the CNS that support neuron homeostasis .…”
Section: Discussionmentioning
confidence: 99%